Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1210/jc.2014-1953
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of Plasma Kisspeptin During the Antenatal Booking Visit Are Associated With Increased Risk of Miscarriage

Abstract: Context:Kisspeptin is a recently identified hormone encoded by the KISS1 gene, playing a critical role in human reproduction. Plasma kisspeptin levels rise dramatically during normal pregnancy due to placental synthesis, which implicates it as a potential tool for assessing risks of pregnancy complications. No previous prospective study has investigated the association between plasma kisspeptin and risk of miscarriage.Objective:The objective of the study was to determine whether a single plasma kisspeptin or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 29 publications
1
72
0
1
Order By: Relevance
“…Kisspeptin levels below 1630 pmol/L during the first trimester were considered a miscarriage biomarker, since women who suffer miscarriages show kisspeptin levels 60% lower than unaffected pregnancies [81].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Kisspeptin levels below 1630 pmol/L during the first trimester were considered a miscarriage biomarker, since women who suffer miscarriages show kisspeptin levels 60% lower than unaffected pregnancies [81].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…14 In humans, the plasma concentration of kisspeptin increases dramatically in the pregnancy, with a 900-fold increase in the first trimester and further increases to over 7000-fold in the third trimester compared to the non-pregnant women. 15 It is most likely that the increase in the total number of trophoblast cells throughout the course of gestation is responsible for the dramatic increase in serum kisspeptin levels. 16 Kisspeptin are mainly derived from placenta, the levels of plasma or serum kisspeptin can probably act as a biomarker for the function of the placenta and therefore viability of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Plasma or serum kisspeptin levels are significantly increased in early pregnancy compared to non-pregnant controls. [13][14][15]…”
Section: Introductionmentioning
confidence: 99%
“…Jayasena and coworkers showed that circulating kisspeptin at antenatal booking correlated with risk of miscarriage (Jayasena et al 2014a), with gestation-corrected kisspeptin being 60% lower in women with a singleton pregnancy compared with unaffected singleton pregnancies (gestation-corrected multiple of median kisspeptin 1.06 ± 0.42 singleton no miscarriage vs 0.42 ± 0.39 singleton miscarriage, P < 0.001 with values representing mean ± s.d.). The relationship of kisspeptin with miscarriage was also demonstrated in twin pregnancies, where death of one foetus was associated with a lower kisspeptin level than those without complications.…”
Section: Implantation and Placental Functionmentioning
confidence: 99%